Conditional Automaticity in Response Selection: Contingent Involuntary Response Inhibition With Varied Stimulus-Response Mapping. (February 2014) - Anderson, Brian A.; Folk, Charles L.
One aspect of effective cognitive control is the ability to withhold contextually inappropriate responses. The inhibition of a response can be elicited by a goal-relevant stop signal, which has been characterized as a voluntary cognitive process. Cases in which inhibition is triggered automatically by a stimulus have been reported but are limited to instances in which the withholding of a response is associated with the same stimulus over repeated trials, which reflects the gradual emergence of automaticity through associative learning. Findings such as these suggest that inhibitory control is driven by two dissociable mechanisms, one that is flexible but deliberate and another that is automatic but inflexibly learned. In the present study, we showed that response inhibition can be involuntarily triggered when stimulus-response mapping varies unpredictably, without contributions from associative learning. Our findings demonstrate that automatic response inhibition can be flexibly conditioned on top-down goals, which has broad implications for theories of cognitive control.